Two-dimensional group-III nitrides and devices: a critical review. (6th August 2021) - Wang, Wenliang; Jiang, Hongsheng; Li, Linhao; Li, Guoqiang
Abstract: As third-generation semiconductors, group-III nitrides are promising for high power electronic and optoelectronic devices because of their wide bandgap, high electron saturation mobility, and other unique properties. Inspired by the thickness-dependent properties of two-dimensional (2D) materials represented by graphene, it is predicted that the 2D counterparts of group-III nitrides would have similar properties. However, the preparation of 2D group-III nitride-based materials and devices is limited by the large lattice mismatch in heteroepitaxy and the low rate of lateral migration, as well as the unsaturated dangling bonds on the surfaces of group-III nitrides. The present review focuses on theoretical and experimental studies on 2D group-III nitride materials and devices. Various properties of 2D group-III nitrides determined using simulations and theoretical calculations are outlined. Moreover, the breakthroughs in their synthesis methods and their underlying physical mechanisms are detailed. Furthermore, devices based on 2D group-III nitrides are discussed accordingly. Based on recent progress, the prospect for the further development of the 2D group-III nitride materials and devices is speculated. This review provides a comprehensive understanding of 2D group-III nitride materials, aiming to promote the further development of the related fields of nano-electronic and nano-optoelectronics.